REPRESENTASI KECANTIKAN PADA PROGRAM PUTERI INDONESIA 2023 DI SCTV : (ANALISIS SEMIOTIKA JOHN FISKE) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The aim of this research is to analyze the representation of beauty in the Puteri Indonesia 2023 program aired on SCTV. This research is descriptive-qualitative using John Fiske's semiotic analysis method, which examines signs to construct meaning within the broadcast, comprising three levels of analysis: reality, representation, and ideology. The data source for this research is the final round broadcast of Puteri Indonesia 2023 uploaded on the Official Puteri Indonesia YouTube channel. Meanwhile, the data collection method used is a literature study, and the data analysis technique employed is John Fiske's semiotics. The results of the study indicate that the Puteri Indonesia 2023 program showcases beauty in line with global standards of femininity and beauty. This is evident from the clothing, makeup, and the way the finalists speak and interact. Additionally, aspects of intelligence and behavior are also evaluated, with the finalists expected to have extensive knowledge and a graceful demeanor. The program uses visual and symbolic elements to create an ideal image of beauty that encompasses physical appearance, intelligence, and behavior. Although the representation of beauty in this program aligns with common beauty standards, the Puteri Indonesia 2023 pageant also shows a slight shift by not merely displaying physical beauty but also expanding the meaning of beauty through the concepts of "brain," "beauty," and "behavior." This research enhances our understanding of how media shapes our perception of beauty through visual and symbolic representation. These findings are expected to be useful for further research on gender and beauty representation in mass media.